Developing Video-Based Learning Media with Problem-Based Learning Approach on Pythagorean Theorem Topic - Wardah Shofiyyah; Abd. Qohar (Edunesia: Jurnal Ilmiah Pendidikan, 2022)
Technology and information development give significant changes to the required human skills in the current era. Educational development is also needed so it is able to prepare the peoples to fulfill nowadays standards, one of it was through the development of learning media that is able to set up students so they have the opportunity to develop the abilities needed. The goals of this study is to develop a mathematics learning video based on problem-based learning approach on the Pythagorean Theorem topic. This is a Research and Development (R&D) study with ADDIE development method. This study’s subjects were 17 eighth-grade students at Junior High School 2 Pandaan. The results show that the problem-based mathematics learning video on the Pythagorean Theorem topic had been successfully developed. Product validation by media expert got a score of 3.71 and product validation by material expert got a score of 3.70 which means that the product is valid. Then for the product practically tests got a score of 3,34 which means that the product is practical. The result of the effectiveness test from the student’s score on the evaluation test after learning using the media shows that 82.4% of all subjects have reached the Minimum Mastery Criteria (KKM) so that the product can be said to be effective. The results indicate that problem-based learning videos can be used as learning media on the Pythagorean Theorem topic.